Analisis Unsur Desain Dan Teknik Pembuatan Gitar Potimarende Sipaholon - Sibuea , Fernando Hyskia; Situmeang , Erik Yonatan; Ritonga , Mardame Nicholas; Charinpatrio Laia, Berlin; Yehezkiel Sinuhaji , Egia; Purba , Mauly (Besaung : Jurnal Seni Desain dan Budaya, 2024)
This study explores the design elements and crafting techniques of Potimarende Sipaholon guitars. Originating from the rich cultural heritage of Sipoholon village, these guitars bear unique characteristics in both design and sound, attracting attention from local and international music enthusiasts. Through qualitative research methods, including interviews and observations, insights into the intricate processes of guitar crafting were obtained. The study delves into the detailed stages of guitar production, from the selection and preparation of raw materials to the finishing touches. Techniques such as wood processing, body construction, and finishing are meticulously executed to ensure the quality and aesthetic appeal of the final product. By understanding and documenting these practices, the research aims to contribute to the preservation of local craftsmanship while inspiring the development of high-quality, culturally relevant guitar products. This endeavor not only strengthens cultural heritage but also stimulates economic growth in the local community.